ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PT MARTINA BERTO TBK PERIODE 2014-2018 - Heru Satria Rukmana; Linda Mariana (Institut Teknologi dan Bisnis Dewantara, 2021)
The results of this study show that the liquidity ratio consisting of current ratio in 2014 was above the industry average and in 2015-2018 was below the industry average, the quick ratio in 2014-2016 was above the industry average and in 2017-2018 was below the industry average, the cash ratio in 2014 was above the industry average and in 2015-2018 was below the industry average. The solvency ratio consisting of debt to asset ratio in 2014 was below the industry average and in 2015-2018 was above the industry average, the debt to equity ratio in 2014 was below the industry average and in 2015-2018 was above the industry average. The ratio of activities consisting of receivable turn over in 2014-2018 is below the industry average, inventory turn over in 2014-2017 was above the industry average and in 2018 was below the industry average, fixed asset turn over in 2014-2018 was below the industry average, fixed asset turn over in 2014-2018 was above the industry average , the total asset turn over in 2014-2018 was below the industry average. The profitability ratio consisting of return on assets in 2014-2018 is below the industry average, return on equity in 2014-2018 is below the industry average and net profit margin in 2014-2018 is below the industry average.